The primary structure of histones H2B from sperm of the sea urchins Parechinus angulosus and Psammechinus miliaris - Strickland, Marie Shields (Department of Molecular and Cell Biology, 2016)
Histones H2B have been purified from sperm of the sea urchin Parechinus angulosus and Psammechinus miliaris. Three H2B variants have been completely sequenced from P. angulosus and two H2B variants from P. miliaris have been partially sequenced. The sequences of the sperm histones H2B are compared to the known sequences Of other H2B histones. The sea urchin sperm histones H2B are all considerably more arginine rich than other histones H2B and contain an extended amino-terminal region containing reiterated pentapeptides.